GROWTH AND YIELD TRAITS OF GROUNDNUT(ARACHIS HYPOGAEA) LINES TREATED WITH HYDROGEN PEROXIDE (FULafia Journal of Science and Technology, 2016)
The response of some growth and yield traits of four  groundnut cultivars, Ms 54-76, ICGV-Sm-42, RmP 12 and Samnut 21 treated with hydrogen peroxide for 24 hours prior to planting was studied using seed treatmentof 0%, 0.5%, 1%, 2% and 3%of hydrogen peroxide (H2O2). The treated seeds were planted in a split plot experimental designing a completely randomised design (CRD) using three replications in University of Calabar, Nigeria. Results showed that more seedlings of Ms 54-76, ICGV-Sm-42 and RmP 12 were established than Samnut 21 at fourteen days after planting. There was a similar variation in the number of days to 50% flowering, number of pods per plant, plant height, number of leaves, number of branches, and weight of pods per plant, shelling percentage and seed weight. The H2O2 incited increase in the seed germination, plant height and in seeds weight from 8 weeks after planting upwards. Generally, ICGV-Sm-42 had the most luxuriant growth and superior yield of the four varieties, followed by Sm-54-76 and RmP 12.ICGV-Sm-42 had the highest response to seed treatment with hydrogen peroxide
Keywords: Hydrogen peroxide; ArachishypogaeaL; physiological stimulant; crop yield; mutagen